POST-INDEPENDENCE ECONOMIC REGULATION IN TIMOR LESTE: NORMATIVE ANALYSIS OF FOREIGN INVESTMENT LAW - Carolina da Cruz (Collegium Studiosum Journal, 2025)
Geographically, Timor Leste is the country closest to Indonesia, making it easier for Indonesian investment to flow to Timor Leste. Therefore, Indonesian investment in Timor Leste will benefit both countries economically, and to maintain stability and security, economic cooperation is one way to achieve peace and prevent conflicts that are prone to occur at the land border between Timor Leste and Indonesia. This research uses a qualitative approach. Furthermore, this research is descriptive-explanatory in nature because it explains narratively and identifies the cause and effect of the issues in the research. Based on the findings, in terms of regulations, Timor Leste has attempted to align its investment legal framework with international principles; however, in practice, the goal of achieving welfare for the majority of the people still faces significant challenges. The foreign investment legal framework in Timor-Leste is normatively designed to guarantee legal certainty and protection for foreign investors, primarily through the applicable Private Investment Law. This law aims to attract investment by establishing clear rules regarding ownership rights, capital transfers, and dispute resolution mechanisms.